Preparation And Characterization Of Intelligent Packaging Based On Torch Ginger Extract And Sago Starch - Lam, Xue Mei (Universiti Sains Malaysia, 2020)
As the concern about the irresponsible usage and disposal of non-biodegradable plastic are arising, researchers are focusing on the substitution of these materials with natural and biodegradable sources. Thus, intelligent packaging has focused on its development as it can exhibit or provide the function of pH changes which can help to detect the freshness of food product. This study was to develop and characterize pH-sensitive films based on sago starch and incorporated with anthocyanin from torch ginger to detect the quality of food products though pH changes. The anthocyanins were extracted with solvent including ethanol and water. The pH-sensitive films were fabricated by casting method with incorporation of different torch ginger extract (TGE) concentration (0%, 10%, 20%, 30%). Thickness, moisture content, moisture sorption isotherm, mechanical properties, water vapour permeability, water solubility, colour, UV-Vis spectroscopy, Fourier Transform Infrared (FT-IR) spectroscopy and morphology of the films were analyzed and investigated. The tensile strength, toughness, young modulus and water vapour permeability decreased after adding TGE, while elongation at break, thickness, moisture content and water solubility increased. The colour variations of pH-sensitive films were measured by a colorimeter after immersion in different pH buffer (pH 4, pH 7, pH 9). The films containing 30% TGE were more suitable for application because it is detectable by human eye over a wide pH range. Thus, the developed pH-sensitive film with torch ginger extract has potential as intelligent packaging for the detection of food spoilage as natural dye was used and the films produced were biodegradable.